ANALISIS PENGENAAN TARIF PAJAK PROGRESIF PADA PAJAK KENDARAAN BERMOTOR THE FOUR MAXIMS(STUDI KASUS SAMSAT KABUPATEN PASAMAN BARAT PROVINSI SUMATRA BARAT) - Muammar Khaddafi; Annesa Dianty Darwin (Jurnal Akuntansi dan Keuangan, 2018)
This study was conducted to determine the imposition of a progressive tax rate on motor vehicle taxes based on The Four Maxims in Pasaman Barat Regency, Sumatra Barat. The method used in this study was a qualitative descriptive method. The type of data used in this study was primary and secondary data. Data collection techniques in this study were interviews, observations, and documentation. The purpose of this study was to determine how to impose a progressive tax rate on motorized vehicle tax based on four principles of tax collection. The results show that the tax principle as still appropriate and relevant to be applied, namely the principles of tax collection proposed by Adam Smith, which are equality, legal certainty, the convenience of payment, and principles efficiency (economic of collection).